2016
DOI: 10.37380/jisib.v6i2.170
|View full text |Cite
|
Sign up to set email alerts
|

Identification and classification of organizational level competencies for BI success

Abstract: Business intelligence is a technology-oriented solution that businesses need tosurvive in today’s competitive and constantly changing market. To gain the benefits of BI systems, it is important to evaluate, assess, and improve factors that have an influence on BI success. Organizational competencies can provide answers to the question of how companies could gain more benefits from BI systems. While investment in BI systems is increasingly growing, measures to evaluate effective organizational competencies lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…It was summarised by Yeoh et al (2008) that the assurance of the integrity and quality of data from the systems from which it is sourced impacts heavily upon BI implementation success. Numerous studies support this idea and show that sources of data positively and directly affect the success of implementation of BI (Wixom and Watson, 2001;Xu and Hwang, 2007;Arnott, 2008;Hwang and Xu, 2008;Yeoh and Koronios, 2010;Olszak and Ziemba, 2012;Anjariny and Zeki, 2013;Dawson and Van Belle, 2013;Işık et al, 2013;Puklavec et al, 2014Puklavec et al, , 2018Grublješič and Jaklič, 2015;Nasab et al, 2015;Mesaros et al, 2016;Pham et al, 2016;Salmasi et al, 2016;Yeoh and Popovič, 2016;Rezaie et al, 2017). Organisational resources As Grandon and Pearson (2004) noted, the term "organisational resources" refers to the degree of technical, financial and human resources within an organisation.…”
Section: Data Sources Systemsmentioning
confidence: 99%
“…It was summarised by Yeoh et al (2008) that the assurance of the integrity and quality of data from the systems from which it is sourced impacts heavily upon BI implementation success. Numerous studies support this idea and show that sources of data positively and directly affect the success of implementation of BI (Wixom and Watson, 2001;Xu and Hwang, 2007;Arnott, 2008;Hwang and Xu, 2008;Yeoh and Koronios, 2010;Olszak and Ziemba, 2012;Anjariny and Zeki, 2013;Dawson and Van Belle, 2013;Işık et al, 2013;Puklavec et al, 2014Puklavec et al, , 2018Grublješič and Jaklič, 2015;Nasab et al, 2015;Mesaros et al, 2016;Pham et al, 2016;Salmasi et al, 2016;Yeoh and Popovič, 2016;Rezaie et al, 2017). Organisational resources As Grandon and Pearson (2004) noted, the term "organisational resources" refers to the degree of technical, financial and human resources within an organisation.…”
Section: Data Sources Systemsmentioning
confidence: 99%
“…Individuals as project members must have appropriate experience, knowledge and skills (Arnott 2008;Rouhani et al 2012;Salmasi et al 2016). According to interviews made by Yeoh et al (2007), they showed that experts agreed that team conformation and the skills of people engaged in the project greatly influenced its implementation success.…”
Section: People and Human Talent Teamsmentioning
confidence: 99%
“…That said, and taking into account that studies on organisational factor's effects on BI systems (as information systems) are still in on initial stages (Salmasi et al, 2016). This research, aims to formulate a conceptual framework of factors previously identified in the OC literature, that could contribute to improve the success rate of BI solutions implementation, from a managerial perspective and not only technical, as applied so far.…”
Section: Introductionmentioning
confidence: 99%